PEMAKAIAN MAJAS DALAM NOVEL ANAK SEMUA BANGSA KARYA PRAMOEDYA ANANTA TOER: STUDI STILISTIKA - Rusdian Noor Dermawan; Joko Santoso (Universitas Sarjanawiyata Tamansiswa, 2017)
The objectives of the research are to find out: (1) the use of figurative language, (2) the function of each figurative language to build the essence of the novel. The research is descriptive qualitative. The research data are the series of events using figurative language. The source is a novel entitled ‘Anak Semua Bangsa’ by Pramoedya Ananta Toer published by Hasta Mitra Jakarta. The research instrument is independent research concentrating on the types and the functions of figurative language. The technique of collecting data is observation; meanwhile, the technique of analyzing data is descriptive qualitative. Based on the analysis, research results can be drawn. Firstly, 70 (97.2%) of 72 figurative languages are a figure of speech. Secondly, 35 (50%) of 70 figure of speech, are simile and epic simile, 6 (8.6%) hyperbolic, and 1 (1.4%) synecdoche. The functions of simile are to express purity, surprise, and description. The functions of metaphor are to raise internal emotion and build concrete sense. The dominant functions of personification are to revive imagination, explain elaboration, and reflect the inanimate objects. The functions of hyperbolic are to strengthen the meaning and empower the impression. The function of synecdoche is to point out the essential part of an object.